Biotechnology development, applications and trade : Caribbean perspective : research paper - Hollingsworth, Wendy (Caribbean Policy Development Centre [S.l.], 2004)
Examines the global applications of biotechnology with respect to the development related to trade and regulatory frameworks. Discusses the relevance of biotechnology application in the Caribbean within the context of GMOs in food, medicine and trade. Analyses regional and national regulatory frameworks with a view to making recommendations for developing systems to benefit from biotechnology and its applications.